Amino acid based hydrogels with dual responsiveness for oral drug delivery - Wang,S; Liu,X; Villar-Garcia,IJ; Chen,R (Macromolecular Bioscience, 2016)
This study reports a series of novel amino acid based dual-responsive hydrogels. Prepared by a facile one-pot 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC) coupling reaction, the solid content, structure, and mechanical behavior of hydrogels could be easily adjusted by changing the concentrations of the polymers and the crosslinkers. With pH-responsive anionic pseudo-peptides as backbones and disulfide-containing l-cystine dimethyl ester as crosslinkers, these hydrogels are able to collapse and form relatively compact structure at an acidic pH, while swelled and partly dissociated at a neutral pH. Further addition of dithiothreitol (DTT) facilitated complete degradation of hydrogels. The high loading efficiency, rapid but complete triggered-release, and good biocompatibility make these hydrogels promising candidates for oral delivery.